Volleyball-specific differences in the running vertical jump - Tai, W. H.; Wang, L. I.; Peng, H. T. (14th International Symposium on 3D Analysis of Human Movement, 2016)
One- and two-legged vertical jumps are often performed in volleyball games. But the contribution from individual leg in one- and two-legged running vertical jump skills in volleyball has not been revealed. The purpose of this study was to determine the differences between one- and two-legged running vertical jumps (1-LRVJ and 2-LRVJ) on the biomechanical characteristics. Ten male college volleyball players voluntarily participated in this study. Two volleyball running vertical jumps were executed randomly. Three trials of each running vertical jump were recorded for each subject. Data were collected using six infra-red Qualisys motion capture cameras at 180 Hz sampling rate and two AMTI force platforms at 1800 Hz sampling rate, respectively. The jump height of 2-LRVJ was significantly higher than 1-LRVJ (P< .05). In take-off phase, knee and hip extension impulse of take-off phase of 1- LRVJ were significantly greater than those of 2-LRVJ (P< .05). These results suggested that 1-LRVJ produced higher leg stiffness than 2-LRVJ. We suggested that one-legged running vertical jump cause great stiffness and impulse of the lower extremity which would be beneficial to the SSC, and practice one-legged running vertical jump was a greater stimulus for training.